Genotype identification of Sengon (Paraseriathes falcataria (L.) Nielsen needs accurate and reliable method for identification. Sixteen individuals of P. falcataria from Okinawa, Japan were used as materials for selecting polymorphic RAPD fragments and for developing SCAR marker whereas confirmation of polymorphisms of the SCARs was conducted using 24 materials from Candiroto Seed Orchard, Indonesia. Forty-eight polymorphic fragments were obtained from screening in 288 RAPD primers. Forty-six ou - VIVI YUSKIANTI; SUSUMU SHIRAISHI (Bogor Agricultural University, Indonesia, 2010)
Genotype identification of Sengon (Paraseriathes falcataria (L.) Nielsen needs accurate and reliable method for identification. Sixteen individuals of P. falcataria from Okinawa, Japan were used as materials for selecting polymorphic RAPD fragments and for developing SCAR marker whereas confirmation of polymorphisms of the SCARs was conducted using 24 materials from Candiroto Seed Orchard, Indonesia. Forty-eight polymorphic fragments were obtained from screening in 288 RAPD primers. Forty-six out of 48 SCAR primers were successfully developed. Examination of the newly-designed of SCAR primer using 24 P. falcataria from Candiroto Seed Orchard, Indonesia found 5 polymorphic SCAR primers. These five SCARs are considered as useful marker for genotype and clone identification within P. falcataria.